Three-dimensional cellular microarray for high-throughput toxicology assays - Lee, Moo-Yeal (National Academy of Sciences, 2008)
We have developed a miniaturized 3D cell-culture array (the Data Analysis Toxicology Assay Chip or DataChip) for high-throughput toxicity screening of drug candidates and their cytochrome P450-generated metabolites. The DataChip consists of human cells encapsulated in collagen or alginate gels (as small as 20 nl) arrayed on a functionalized glass slide for spatially addressable screening against multiple compounds. A single DataChip containing 1,080 individual cell cultures, used in conjunction with the complementary human P450-containing microarray (the Metabolizing Enzyme Toxicology Assay Chip or MetaChip), simultaneously provided IC(50) values for nine compounds and their metabolites from CYP1A2, CYP2D6, and CYP3A4 and a mixture of the three P450s designed to emulate the human liver. Similar responses were obtained with the DataChip and conventional 96-well plate assays, demonstrating that the near 2,000-fold miniaturization does not influence the cytotoxicity response. The DataChip may therefore enable toxicity analyses of drug candidates and their metabolites at throughputs compatible with the availability of compounds at early-stage drug discovery.